Hardiness dan Burnout pada Petugas Penyidik Kepolisian Negara Republik Indonesia (Polri) - A. Eka Septilla; Nadya Syifa Maryanti (Fakultas Psikologi Universitas Pancasila, 2019)
This study examines the role of hardiness on burnout in Indoensian national police investigators. 142 Indonesian national police investigators age 25-40 years old were collected using the Maslach Burnout Inventory (MBI) and Occupational Hardiness Questionnaire. Both of the measuring instruments were valid with a reliability of 0.70-0.75. The research method was a non-experimental, quantitative method. All data were analyzed using correlational technique which showed that individuals with higher hardiness score tends to have low burnout score. The results indicated that hardiness has a contribution of 67.3% to burnout, while the rest was contributed by other factors. Therefore, hardiness is one of the personalities that must be possessed by Indonesian national police investigators.